Characterization of and risk factors for HIV-1 resistance mutations following first line antiretroviral failure in the southern African private sector - Lutaaya, Leonard Edgar (Department of Medicine, 2017)
Background: First-line antiretroviral therapy (ART) regimen choices have evolved over the past 15 years in South Africa. Many patients develop HIV drug resistance mutations when they fail first-line ART. The effect of different drug regimens and other patient related factors on drug resistant mutations selected at first line failure are not well characterised in Southern Africa with its predominantly subtype C epidemic. Objectives: To characterize HIV resistance mutations in patients failing first-line ART in the private sector in Southern Africa, and risk factors associated with resistance and particular resistance mutations. Methods: This was a retrospective observational study linking two databases. One database was that of the Aid for AIDS (AfA) disease management programme (for clinical and ART regimen data) and the other was that of Lancet Laboratories where HIV genotypic sequence data were stored. Variables included in analyses were age, gender, province, WHO stage at time of resistance testing (HIVDR), duration of ART at HIVDR, prior monotherapy or dual therapy, viral load and CD4 count prior to starting ART, viral load and CD4 count at HIVDR, duration that the viral load was >400 copies/ml prior to HIVDR and HIV subtype. Data on patients who had a resistance test between 2008 and 2014 while failing first line ART was extracted from these databases. Fisher's exact test and Chi-squared test were used to analyse categorical variables and Wilcoxon rank sum test for continuous variables. For multivariate analyses, logistic regression models were used. Results: Patients who registered with AfA between 1998 and 2013 and had a resistance test performed whilst experiencing viral failure on a non-nucleoside reverse transcriptase inhibitor (NNRTI) regimen with no history of prior failure on a protease inhibitor (PI) regimen were included: 265 (95.3%) patients had a reverse transcriptase mutation of any kind, 253 (91%) had an NNRTI mutation and 246 (88.5%) had a nucleoside reverse transcriptase inhibitor (NRTI) mutation (n=278). The commonest mutation was the M184V mutation (80.6%), 44.2% had at least one thymidine analogue mutation (TAM) and 42.1% had the K103N/S mutation. Notably there was a median of 18 months during which the viral load was not suppressed prior to the resistance tests, which likely contributed to the high prevalence of mutations. A total of 83 (29.9%) patients were found to have the K65R mutation, 72 of these patients were on tenofovir (TDF) at the time of resistance testing demonstrating the strong association between TDF and the K65R mutation. Conclusions: The mutational patterns observed in our study and their prevalence were similar to those noted in previous studies done within the region's public sector. There was a high prevalence of the K65R mutation in patients failing TDF-containing regimens. A longer duration on ART and failing ART were correlated with an increased number of TAMs.